Utilization of interdisciplinary in-hospital early rehabilitation in COVID-19 patients - a multicenter cohort study in the National Pandemic Cohort Network (NAPKON) in Germany - Max E. Liebl; Anett Reisshauer; Dana Loudovici-Krug; Philipp Baumbach; Katharina S. Appel; Sabine Blaschke; Johanna Erber; Ilka Grewe; Marina Hagen; Ekaterina Heim; Sina M. Pütz; Kristin Lehnert; et al. (PLoS ONE, 2025)
Background Early rehabilitation in acute hospitals aims to prevent immobilization-related complications and improve the functional capacity of patients with severe or critical illness. Early rehabilitation can be a useful concept to improve functioning in COVID-19 patients. However, literature concerning early in-hospital rehabilitation in COVID-19 patients is scarce. Aim To analyze the utilization of in-hospital interdisciplinary early rehabilitation (IER) in COVID-19 patients and characterize the sample of IER patients. Design Prospective cohort study. Setting Hospitalized COVID-19 patient cases. Population This study used data from the National Pandemic Cohort Network (NAPKON) in Germany. Methods IER utilization rates were retrieved. Demographic and clinical data from hospitalized COVID-19 patients who had received IER during the course of their treatment were evaluated. Results Out of the 2,644 patients in the Cross-Sectoral Platform (German abbreviation: SUEP) cohort, 0.79% [95% CI: 0.51% to 1.22%] received IER during their stay in an acute care hospital. Among the subgroup of patients who had previously been treated in intensive care, 2.13% [95% CI: 1.16% to 3.63%] received IER. The most common comorbidities were cardiovascular diseases (66.7%) and neurological/psychiatric diseases (36.1%). The small sample size limited further analyses. Conclusion The low rate of early rehabilitation in acute hospitals for COVID-19 patients indicates an unmet need, particularly in severe cases. Structural changes in the health system are needed to close this gap. The WHO and the German Medical Council have recently acknowledged the necessity of early in-hospital rehabilitation and have issued a call for its implementation in acute hospitals.